2020
DOI: 10.1038/s41598-020-72086-4
|View full text |Cite
|
Sign up to set email alerts
|

Origin and structure of liquid crystalline Blue Phase III

Abstract: We report here an off-lattice NVT molecular dynamics simulation study of a system of polar chiral ellipsoidal molecules, which spontaneously exhibits Blue Phase III (BPIII), considering coarse-grained attractive-repulsive pair interaction appropriate for anisotropic liquid crystal mesogens. We have observed that suitable selection of chiral and dipolar strengths not only gives rise to thermodynamically stable BPIII but novel Smectic and Bilayered BPIII as well. Further, we have demonstrated that the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…More recently, two interesting simulation studies on BPIII have been reported. The study reported by Paul and Saha supports the theoretical proposition of the spaghetti-like arrangement of the double-twist cylinders as a model of BPIII [ 24 ]. Pišljar and Muševič et al reproduced the bulk BPIII of mutually enmeshed structures of singular defect lines (yellow) and skyrmion filament-DTCs ( Figure 5 ) [ 46 ].…”
Section: Phase Structure Of Bpiiisupporting
confidence: 66%
See 3 more Smart Citations
“…More recently, two interesting simulation studies on BPIII have been reported. The study reported by Paul and Saha supports the theoretical proposition of the spaghetti-like arrangement of the double-twist cylinders as a model of BPIII [ 24 ]. Pišljar and Muševič et al reproduced the bulk BPIII of mutually enmeshed structures of singular defect lines (yellow) and skyrmion filament-DTCs ( Figure 5 ) [ 46 ].…”
Section: Phase Structure Of Bpiiisupporting
confidence: 66%
“…More recently, two interesting simulation studies on BPIII have been reported. Th study reported by Paul and Saha supports the theoretical proposition of the spaghetti-lik arrangement of the double-twist cylinders as a model of BPIII [24]. Pisľjar and Musěvič al.…”
Section: (A)mentioning
confidence: 53%
See 2 more Smart Citations
“…1G). [28][29][30][31][32] Fig. 1 As both BPI and BPII exhibit cubic symmetries with lattice parameters corresponding to the wavelength range of visible light, their inherent topologies achieve an adjustable photonic bandgap.…”
Section: Monirosadat Sadatimentioning
confidence: 99%